Pattern rupture and channeling effect by alternating radial displacement. (15th June 2023) - Chou, Chi-Chian; Huang, Wei-Cheng; Chen, Ching-Yao
Highlights: The first experimental study of alternating injection of two immiscible fluids in Hele-Shaw cell is carried out. Two unique features, i.e., pattern rupture and channeling effect, are observed. Inconsistent trend of interfacial length is resulted from the two unique features. Experimental results are verified by numerical simulations. Abstract: Effect of alternative injection to immiscible fingering instability in a Hele-Shaw cell (or porous media) is studied experimentally and numerically. The injection alternation of less/more viscous fluid results in fluid layer of fingering/circular interface, respectively. Correspondingly to the interrupted supply of less viscous fluid and continuous expansion by the following circular interface, the fingering layer is ruptured to form a unique pattern of separated fluid islands. In addition, the pattern of the most inner fingering layer of each alternation emerges with great similarity. The repeatability of these newly emerging patterns indicates preferred flow paths of injected less viscous fluid, referred to as channeling effect. The features of pattern rupture and channeling effect caused by injection alternation result in inconsistent influence to the interfacial length, which is important to many applications such as reaction and dissolution. The interfacial length increases significantly by injection alternation in the cases of less unstable conditions because of additional fluid-fluid interfaces. Nevertheless, the azimuthally ruptured fluid islands and active finger coalescences along the radial channels reduce the interfacial length. For cases of extremely vigorous fingering (higher viscosity contrast or larger injection rate) associated with frequent alternation, the overall interfacial length is reduced even with more additional fluid-fluid interfaces. All the above qualitative and quantitative observations in experiments are numerically verified by simulations.